Development of sexual organs and fecundity in Octopus vulgaris Cuvier, 1797 from the Sardinian waters (Mediterranean Sea) - CUCCU, D.; MEREU, M.; PORCU, C.; FOLLESA, M.C.; CAU, AL.; CAU, A. (Mediterranean Marine Science, 2013)
In this paper we report information about the sexual maturity process of 245 Octopus vulgaris specimens (75 females and 170 males) from the Mediterranean Sea. For both sexes, six stages of sexual maturity (immature, developing, maturing, mature, spawning, and spent) are identified on the basis of macroscopic and microscopic observations of the reproductive system and linked with some reproductive indices. A good correspondence between gonad appearance and its histological structure is observed, highlighting, in females, how oviducal gland morphology plays a crucial role in the macroscopic evaluation of maturity. The Gonadosomatic and Hayashi indices, in the two genders, and the Oviducal Gland index in females alone do not allow distinguishing all the stages in an irrefutable way. Data on the potential fecundity, oocyte and spermatophore size are reported and compared with literature. In addition, spermatophore components are also computed. The results reported in this paper lead to easy identification of the different phases of sexual maturation of O. vulgaris and could constitute an important tool for defining assessment models in view of sound management of this species.